(untitled) (Fiep Bulletin - online, 2014)
The levels of daily physical activity are reduced during preadolescence and this predisposes young people to overweight and obesity [1,2]. The levels of physical fitness of young people are in relation to BMI [3]. The aim of the study was to examine the physical activity levels and motor performances in relation to BMI . The Physical Activity Questionnaire for Children (PAQ_C) [4] and tests on standing long jump and 20-m sprint[5,6], have been completed by a sample of 161 boys and 141 girls, aged 11 to 12 years, divided into two groups, normal weight and overweight / obese, according to the cut off of Cole [7]. Apart from the descriptive statistics (M±DS), Student’s T Test was carried out, in order to highlight the significant differences within the group. The significativity index was set to p <.05. ANOV A 2 (group) highlighted considerable differences in the following tests: the males and females of the group Nw showed superior motor performances compared to the group Ow-Ob in standing long jump (p <.001) and in speed test (M: p <.001; F: p<.05). In self-report PAQ_C the group Nw males and females showed higher scores than the group Ow-Ob (p <.05).Physical education at school increases the levels of physical activity, motor development and prevents obesity in young. The teaching styles are of significant importance.